Coupled effects of stress-induced compaction and competitive adsorption on O2 displacement by N2/CO2 and gas transport in loaded crushed coal - Xiyang Fang; Bo Tan; Haiyan Wang; Zhongbei Li; Hao Lu; Kaimin Zhang; Fang Zhou (Fuel, 2027)

Seismic reservoir characterization of deep carbonates under complex overburden: a lithofacies-association zonation workflow, Longwangmiao Formation, Sichuan Basin - Lei Tan; Yuanzhi Zhou; Junliang Li; Linzhi Zhang; Ya Zhang; Pingchao Fang; Minzhi Zhang; Bowen Liu; Longyan Yin; Lin Qiao; Mingzhi Kuang; Hong Liu (Carbonates and Evaporites, 2026)

Diverse bioactive metabolites from Callicarpa longifolia var. floccosa: terpenoids, polyketide, and callilongiflocin A as a potent anti-inflammatory diterpenoid targeting IL-17/TNF-α/MAPK signaling with anti-psoriatic activity - Ting Liu; Xiao-Lu Wu; Lian-Chun Li; Lan-Fang Tan; De-Sheng Ning; Yu-Xia Fu; Zheng-Hong Pan (Phytochemistry, 2026)

Multi-component crustal recycling recorded by LiMg isotopes in Emeishan mafic–ultramafic layered intrusions with implications for Fe–Ti–V metallogeny - Yan-Fang Luo; Dong-Bo Tan; Hai-Ou Gu; Yang-Yang Wang; He Sun; Dong-Yong Li; Qian-Ling Zhou; Shi-Chu Zhao; Yilin Xiao (Lithos, 2026)

Behaviour of concrete-filled circular TIG-welded aluminium alloy tubes under axial compression - Yong Fang; Mingxuan Li; Qinghua Tan; Shichao Yan; Yuyin Wang; Hua Yang (Engineering Structures, 2026)

Tire wear particle leachate-induced hepatotoxicity in Carassius auratus: Associations with gut microbiota dysbiosis and lipid metabolism disorder - Peng Fang; Yongyu Hu; Maolin Zhang; Yuanyuan Tan; Siwen Li; Fang Xiao (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2026)

Low-loss AgReMo2O8 (Re = Y, Yb) LTCC ceramics designed by Ag+ common-ion effect for dielectric resonator antenna applications - Jian Bao; Jing Guo; Da Tian; Zhen Fang; Zhen-Tao Wang; Yang Liu; Yang Gao; Cai-Hong Zhang; Biao-Bing Jin; Andreu Cabot; Li-Xia Pang; Kar Ban Tan; et al. (Chemical Engineering Journal, 2026)

Gestational NO₂ exposure induces anxiety‐ and depression-like behaviors in mice via hippocampal PTGDS-PGD2 activation and tryptophan metabolism reprogramming - Wei Li; Xinying Wang; Sixuan Tang; Shuzi Ye; Ruicheng Zeng; Rongrong Zhang; Chenchen Liu; Yuanyuan Tan; Di Ji; Fang Xiao (NeuroToxicology, 2026)

nZVI-rGO/geotextile bioretention systems for enhanced and stable nitrate removal under carbon-limited stormwater conditions: Performance and mechanistic insights - Zehua Li; Zhichun Duan; Meipeng Jian; Yuanping Fang; Yingming Xu; Yalun Wang; Chaohong Tan; Haiyan Li (Chemical Engineering Journal, 2026)

Enhanced ORR performance of A/B-site co-doped La0.5Cs0.1Sr0.4Co0.15Fe0.8Ni0.05O3−δ perovskite cathode via NiO secondary phase synergy for SOFCs - Yan Fang; Fozia Sultana; Xiaoqing Yan; Selvi Mushina; Zhang Lili; Mingwu Tan; Tong Wei; Renhong Li (Chemical Engineering Journal, 2026)

A novel dual-mode Fluorescence/Colorimetric Aptasensor Based on NH2-MIL-88B(Fe)/CDs-Apt for Kanamycin Detection - Huijing Hou; Mingming Luo; Fang Li; Yijun Tan; Ruowei Liu; Longping Xu; Yanwen Feng; Xiangli Guo; Zijian Wu (Journal of Fluorescence, 2026)

Selective catalytic oxidation of ammonia by efficient FeOx in coal ash: insights from experimental and DFT studies - Yili Zhang; Su Zhang; Binxin Fang; Liming Cui; Yixiang Zhang; Wenzhen Zhang; Houzhang Tan; Ming Li; Xuebin Wang (Fuel, 2026)

Differential analysis of lipid profiles in natural Calculus Bovis and Bovis Calculus Sativus by UHPLC-MS/MS - Qiang Mao; Huan Zhong; Wan-Li Liang; Jin Dai; Rui-Ting Huang; Yi-Di Wang; Di-Yang Sun; Kai Tang; Long-Fei Xia; Hai-Biao Gong; Yi-Fang Li; Wan-Yang Sun; et al. (Journal of Natural Medicines, 2026)

Isolation and genomic analysis of a novel Pseudomonas phage from karst cave in China - Xiu Chen; Zheng Fang; Shixia Li; Qingshan Wu; Wenjing Liu; Lan Xiang; Qiuping Liu; Leitao Tan; Qingbei Weng (Archives of Virology, 2026)

Glaucoma Drug Target Prioritisation Informs Disease-specific Therapeutic Potentials of Targeting SMAD4 - Chaohui Bao; Tingting Tan; Yisheng Yang; Chenxu Gao; Kaiwen Liu; Chang Lu; Rulin Guo; Zheng Wang; Jiantao Shi; Jinchen Li; Ming Ni; Hai Fang; et al. (Phenomics, 2026)

Full cost accounting for biomethane from high-concentration organic wastewater - Shuyun Li; Chenxuan Wang; Siqi Wang; Zhiwei Li; Raymond R. Tan; Fang Wang; Xiaoping Jia (Journal of Cleaner Production, 2026)

Uniaxial tensile strain-insensitive and zero-birefringence cellulose acetate films via atom-economic isocyanate modification - Zhouhang Lei; Wenhao Guo; Xingyue Fang; Zhengqi Tan; Heng Xue; Xueyu Li; Liangbin Li (Carbohydrate Polymers, 2026)

Mechanical Properties of Glycated Cracked Articular Cartilage Under Uniaxial and Cyclic Tensile Loading - Li-Lan Gao; Yi Fang; Xiang-Long Lin; De-Zhao Kong; Yan-Song Tan; Rui-Xin Li; Kai Sun; Chun-Qiu Zhang; Yanliuxing Yan (Annals of Biomedical Engineering, 2026)

Soil water vapor adsorption and condensation governed by groundwater depth and vadose zone lithology in arid and semi-arid regions - Ran Li; Haibo Feng; Yanhong Xue; Jianwei Zhou; Lei Fang; Danhui Su; Xiaoming Zheng; Siqi Tan; Huyuan Zheng; Yongxiang Ma (Journal of Hydrology, 2026)

Mercury anomalies in Paleozoic–Mesozoic strata of South China: Implications for global volcanism and mass extinctions - Minglong Li; Liang Qiu; Can Chen; Keyuan Xu; Haiyan Tan; Deshun Zheng; Xilin Fang (Gondwana Research, 2026)

Natural deep eutectic solvents (NADESs) as cryoprotectant for Lactiplantibacillus plantarum YR07: antifreeze mechanisms and applications - Sha sha Zheng; Li jun Tan; Qiong Pan; Yu fei Zhang; Wen di Zhang; Li fang Zou; Wei Cui; Yu Zhou; Ying ying Hu; Bao cai Xu (Food Research International, 2026)

Deoxyinosine enhances GnRH biosynthesis by promoting estradiol production in the hypothalamus and ovaries - Siyu Li; Yutian Wang; Yueyang Meng; Yuxin Fan; Jiayu Tu; Xiangzhou Zeng; Shuang Cai; Chengquan Tan; Shihai Zhang; Fang Chen; Chuanjiang Cai; Xiangfang Zeng (Science China Life Sciences, 2026)

Multiscale thermal response and hazardous hydrocarbon gas evolution during low-temperature coal oxidation in sealed fire zones - Bo Tan; Hao Lu; Zhenrong Li; Saiyi Gao; Jinliang Li; Xiyang Fang; Jun Zhou (Journal of Cleaner Production, 2026)

Al-doped α-MnO2 for low-temperature catalytic oxidation of formaldehyde - Zhengnan Lin; Zhao Zheng; Junchen Li; Cheng Zhang; Qingyan Fang; Peng Tan; Gang Chen (Journal of Environmental Chemical Engineering, 2026)

Exploring the hyperspectral response of leaf chlorophyll content under canopy structure and soil background variability - Zhenwang Li; Zhaokai Ma; Ruisi Bao; Wenli Fang; Quan Tang; Erya Yu; Xiaodong Song; Changwei Tan (European Journal of Agronomy, 2026)

PQQ Modulates Cell Cycle and DNA Replication Programs to Alleviate Replicative Senescence in Human Umbilical Cord Mesenchymal Stromal Cells - Siyun Wang; Fang Lu; Chunxia Tan; Yibo Li; Jiutang Sun; Yuqi Sun; Xiaoyun Chen; Tao Lu (Stem Cell Reviews and Reports, 2026)

Global Potential and Trade‐Offs of Conservation Tillage for Crop Productivity and Ecosystem Services - Wanyang Zhang; Linchuan Fang; Wenju Zhang; Chaoqun Wang; Tianyi Qiu; Xiaokun Li; Min Huang; Bolin Li; Ling Xia; Lai Peng; Yifeng Xu; Xiaoyong Wu; et al. (Global Change Biology, 2026)
Conservation Agriculture (CA) is pivotal to achieve sustainable intensification, yet the global efficacy of its core practice, conservation tillage (CT), remains debated regarding the trade‐offs between crop productivity and ecosystem services across diverse environmental contexts. Here, we conducted a second‐order meta‐analysis, synthesizing 69 published meta‐analyses, to elucidate the context‐dependent drivers regulating the “win‐win” outcomes of CT. Globally, CT reduced greenhouse gas (GHG) emissions by 5%, increased soil organic carbon sequestration by 21%, increased soil fertility by 11%, and reduced soil erosion by 12%, all while maintaining crop yields comparable to conventional tillage. However, CT can also emerge as a partial trade‐off between crop yields and ecosystem services, notably between crop yield and GHG mitigation. These trade‐offs were strongly regulated by climatic and edaphic conditions as well as management intensity. For instance, strong synergies between crop productivity and multiple ecosystem services were more pronounced in (semi‐)arid regions characterized by low temperatures and low precipitation, as well as in coarse‐textured alkaline soils. Furthermore, integrating CT with residue retention and crop rotations maximized these synergies, mitigating potential yield penalties. Collectively, our synthesis demonstrates that context‐specific refinement of CT implementation is essential to reconcile agricultural productivity with ecosystem services, thereby advancing climate‐resilient agricultural systems globally.

A new domoic acid-producing diatom Nitzschia cf. inordinata (Bacillariophyceae) in Chinese coastal waters - Fang Yue; Biaobiao Niu; Guanchao Zheng; Yuichi Kotaki; Nina Lundholm; Huanchang Dong; Xiaofeng Huang; Xiaohang Jiang; Zhijun Tan; Yang Li (Journal of Oceanology and Limnology, 2026)

A novel approach to monitor peanut equivalent water thickness through modular training and transfer learning of an improved PROSAIL model using a Wasserstein generative adversarial network - Shiyuan Liu; Yumeng Zhou; Weiguang Yang; Jiangtao Tan; Xi Li; Zhenhui Xiong; Zewu Fang; Hong Li; Yifei Chen; Yubin Lan; Shubo Wan; Jianguo Wang; et al. (Computers and Electronics in Agriculture, 2026)

A synergistic ligand complexation-electrocatalysis strategy for efficient uranyl extraction from nuclear wastewater - Juanlong Li; Hong Li; Yanxiang Kong; Sergey V. Churakov; Hangxi Liu; Yuxuan Li; Jiayi Zhang; Zedong Zhou; Ming Fang; Xiaoli Tan; Guixia Zhao; Laurent Charlet; et al. (Water Research, 2026)

Integrated multi-sectoral approach for planning of carbon capture and storage projects - Huizhong Zhang; Tianyuan Zhou; Siqi Wang; Zhiwei Li; Raymond R. Tan; Xiaoping Jia; Fang Wang (Resources, Conservation and Recycling, 2026)

Synergistic oxygen vacancy and multivalence in Co/Cu-ZIF/V₂O₅ nanozyme enable ultrasensitive colorimetric detection of ascorbic acid and epigallocatechin gallate - Mingxuan Liu; Yuanjuan Bai; Jianming Tan; Zetong Mei; Kun Du; Gonggang Liu; Li Liu; Shanshan Chang; Ling Fang; Jinbo Hu (Food Chemistry, 2026)

First evidence of CP violation in beauty baryon to charmonium decays - R. Aaij; A.S.W. Abdelmotteleb; C. Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2026)

Moss biocrusts enhance hydrological functionality on engineered slopes: pore restructuring, water retention, and hydrophobicity compensation in humid subtropical ecosystems - Chen Wang; Jiaqi Tan; Zhou Fang; Yingjie Zhang; Ming Luo; Binbin He; Shaoxian Song; Li Wu; María Luciana Montes; Delong Meng; Ling Xia (Journal of Hydrology, 2026)

Self-heating characteristics of rice straw in a 120-L insulated container: Experiments & CFD studies - Mingshuo Cui; Xinke Chen; Yuan Li; Tingting Luo; Qianhua Huang; Qingyan Fang; Peng Tan; Cheng Zhang; Gang Chen; Chungen Yin (Fuel, 2026)

Nanogel-encapsulated Rosa roxburghii Tratt fruit polyphenols ameliorated ulcerative colitis by regulating gut microbiota and PI3K/Akt and NF-κB pathways - Mingxiu Long; Hui Wang; Fang Zhang; Yaoqi Ran; Yongfu Li; Jingwen Luo; Zhaojun Chen; Zhuxi Tian; Shuming Tan; Xiong Liu (Food Research International, 2026)

A new isoprenyl-phenol-type meroterpenoid from mangrove endophytic fungus Aspergillus sp. GXNU-Y65 - Fan-Fan Wang; Guo-Bao Huang; Cai-Hong Lu; Li-Jun Chen; Hui-Zhen Chen; Meng-Qin Luo; Ping-Fang Tao; Ming-Xiong Tan; Feng Qin (Natural Product Research, 2026)

Paleoclimatic fluctuations as drivers of karst plant diversification in southern China - Ke Tan; Long-Fei Fu; Ming-Xun Ren; Xiao-Juan Li; Zi-Bing Xin; Ren-Fen Wang; Pramote Triboun; Truong Van Do; Fang Wen; Yi-Gang Wei (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

Evaluating technical soil derived from lithium mica residue: Integrating soil quality and life cycle assessment for functional performance and environmental sustainability - Yanqi Li; Zi Guo; Xinyan Lv; Xin Liao; Guilan Duan; Liping Fang; Xiaoliang Li; Xiao Tan; Aijun Lin (Journal of Cleaner Production, 2026)

Dietary Haematococcus pluvialis powder enhances the growth and hepatopancreas and intestinal health of Leuciscus waleckii via NF-κB/Nrf2 pathway - Bei Xi; Tong-Tong Tan; Qi Sun; Ming-Xuan Zhang; Jia-Jing Wang; Rui Zhu; Deng-Lai Li; Li-Fang Wu (Fish & Shellfish Immunology, 2026)

Tetrahydrocurcumin for Major Depressive Disorder with Therapeutic Potential and Mechanistic Insights from Clinical and Preclinical Studies - Ying Guo; Jianping Xie; Haiyun Luo; Yun Yuan; Fang Long; Jingyuan Meng; Hui Tan; Yuanping Li; Bibo Cai; Meiling Chen; Liyan Yang; Jingmei Zhong; et al. (Molecular Neurobiology, 2026)

Nuclear transport factor IPO4 modifies localization by PCV2 and facilitates viral replication - Cui Lin; Chengcheng Wu; Fanfan Zhang; Na Li; Haiqin Li; Lihan Tao; Jia Tan; Yanbing Zeng; Shaopei Fang; Quanyong Zhou (Veterinary Microbiology, 2025)

Precise measurements of the cosmic ray proton energy spectrum in the “knee” region - Zhen Cao; F. Aharonian; Y.X. Bai; Y.W. Bao; D. Bastieri; X.J. Bi; Y.J. Bi; W. Bian; A.V. Bukevich; C.M. Cai; W.Y. Cao; Zhe Cao; et al. (Science Bulletin, 2025)

Petrogenesis of Triassic intermediate-felsic intrusions from three skarn tungsten deposits in the East Kunlun Orogenic Belt, NW China: Evidence from zircon U Pb geochronology, petrochemistry, and Hf isotopic characteristics - Yan Tan; Jin-Xiang Li; Fang Xu; Yan-Qian Yang; De-Xin Zhang; Hua-Liang Lai; Sheng-Qiang Ma; Shun-Long Yang; Yi-Jun Yang; Chen Wu; Ya-Hui Yue; Chao Wang; et al. (Lithos, 2025)

Propagation patterns of different degree meteorological droughts across the Yangtze River Basin: a three-dimensional drought feature identification approach with Copula modeling - Lisong Xing; Ruxin Zhao; Hongquan Sun; Zhuoyan Tan; Qingqing Fang; Ming Li; Krishnagopal Halder; Amit Kumar Srivastava (Journal of Hydrology, 2025)

Bioactive pterostilbene encapsulated in zein via an in-situ co-precipitation strategy for efficient antimicrobial and fruit preservative - Chunli Fang; Zhinan Fu; Nan Wei; Jia Wei; Shuying Li; Ting Feng; Zicheng Tan; Junyou Wang; Bin Wu; Xuhong Guo (Food Hydrocolloids, 2025)

Emission estimates of ozone-depleting hydrochlorofluorocarbons for China inferred from new observations and inverse modeling - Ye Chen; Xiaoyi Hu; Kuang Xiao; Xiao Zhang; Mingzhu Li; Tong Ye; Bowei Li; Mingrui Ji; Bo Yao; Haibo Yu; Xuekun Fang; Li Tan; et al. (Atmospheric Environment, 2025)

Co-application Nitrogen and Potassium Fertilizer Enhances Nutrient Uptake and Quality of Hylocereus Undulatus by Changing Soil Properties in Karst Regions - Ting Chen; Shuhua Lu; Yanfang Tan; Bin Wang; Fang Lu; Jianxing Li; Fuzhao Huang; Rong Huang (Journal of Soil Science and Plant Nutrition, 2025)

Disentangling natural and anthropogenic influences on the spatial variability of soil cadmium contamination - Jing Geng; Yong Yu; Qiuyuan Tan; Guoxu Li; Huajun Fang; Yifan Guo; Shulan Cheng (Environmental Pollution, 2025)

Erosion and roads: A review - Yuyu Zhai; Haiyan Fang; Zuoli Wu; Xing Gao; Chaoyue Li; Andrey Zhidkin; Gefei Tan (Earth-Science Reviews, 2025)

New lignans from Phyllanthodendron dunnianum - Li Xu; Jian-Bing Tan; Yu-Ting Zheng; Zi-Huan Sang; Si-Yu Qin; Yuan-Tao Huang; Mei-Fang Li; Zhen-Xing Zou (Natural Product Research, 2025)

Downward migration of functional microorganisms for nitrogen removal in soil layer of bioretention system under rainfall event - Houkun Wei; Fuguo Qiu; Yu Cheng; Yuqi Pan; Yulin Li; Yuanping Fang; Chaohong Tan; Haiyan Li (Journal of Environmental Chemical Engineering, 2025)

The effect of uracil on the freeze-drying survival rate of Lactiplantibacillus plantarum YR07 based on transcriptome analysis - Sha-sha Zheng; Wen-di Zhang; Li-jun Tan; Li-fang Zou; Ying-ying Hu; Liu Yang; Bao-cai Xu (Food Microbiology, 2025)

Genetic burden and multidimensional predictors in prenatal diagnosis of fetal congenital diaphragmatic hernia - Ruibin Huang; Fang Fu; Shanshan Mei; Liyuan Liu; Wei Zhong; Jin Han; Qiuxia Yu; Hang Zhou; Chunling Ma; Li Zhen; Min Pan; Qiong Deng; et al. (Human Genetics, 2025)

DEHP and its metabolite MEHP exposure impairs endometrial decidualization during early pregnancy via up-regulation of Mtmr6 - Li-Ping Tan; Liu Yuan; Yan Zhang; Jun-Lin He; Xin Yin; Yi-Dan Ma; Xue-Mei Chen; Wei-Ke Li; Fang-Fang Li; Ru-Fei Gao (Reproductive Toxicology, 2025)

Dual responsive fluorescent probe for exploring hypochlorite and sulfur dioxide in different heavy metal ions related stress models - Li Zhang; Jiangkun Tan; Xintong Yang; Shujing Fang; Shaoyu Wei; Shudi Liu; Liangwei Zhang; Xiaoyan Wang; Lingxin Chen (Journal of Hazardous Materials, 2025)

Construction of Brönsted sites on pyrite surface via plasma technology for efficient hydrolysis of microcystins-LR - Qing Zhang; Yuting He; Jing Zhang; Yadong Li; Yanfen Fang; Yunzhi Tan (Journal of Environmental Sciences, 2025)

Lithium-doped silicon-hydroxyapatite nanowires alleviate early bone loss in periodontitis via γδ T cell modulation - Zhiyu Zhu; Ruomei Li; Peng Mei; Cheng Zhu; Tiancheng Li; Yixin Li; Wenduo Tan; Yueyi Yang; Yu Jin; Weiming Guo; Runzhe Fang; Lunguo Xia; et al. (Chemical Engineering Journal, 2025)

Research on the path of atmospheric pollutants and greenhouse gas cooperative control in megacities - A case study of Chengdu - Zihang Zhou; Chengwei Lu; Ye Deng; Qinwen Tan; Xia Jiang; Bin Zhao; Fei Fang; Hefan Liu; Danlin Song; Xiaoling Zhou; Xuan Liu; Xin Zhang; et al. (Atmospheric Pollution Research, 2025)

Unraveling the diversity of bile acid modifications by integrative mass spectrometry approaches - Nan Xing; Yu-Fei Wang; Xue Ding; Hong-Li Tan; Yi-Fang Li; Guo-Xiang Sun; Rong-Rong He; Wan-Yang Sun (Science China Life Sciences, 2025)

Effects of Different Short-term Organic Fertilizer Management on Bacterial and Fungal Communities in a Sweet Potato Soil - Jie Zhu; Haixia Wen; Xiuli Su; Shunlin Tan; Zhiguo Fang; Ruiqi Li; Wenjian Wang; Jie Zhang (Journal of Soil Science and Plant Nutrition, 2025)

One-step preparation of carbon quantum dots/silver nanoclusters and ratio-fluorescence detection of mercury ions (II) - Hang Yu; Xiaopei Li; Pengyuan Yin; Shuju Fang; Jie Ma; Yanzhi He; Wenrong Yang; Wei Tan; Shaoqing Li (Process Safety and Environmental Protection, 2025)

Interactions for exposure to fine particulate matter and multiple time-period cold spells on influenza: A multi-center case-crossover study - Shouxin Peng; Bin Fang; Siyu Gan; Yuxuan Tan; Wei Liang; Zhaoyuan Li; Xinlan Chen; Jiahui Tong; Zhongyang Chen; Bingbing Chen; Feifei Liu; Hao Xiang (Journal of Hazardous Materials, 2025)

Pinch analysis for water-energy nexus in urban water systems - Huizhong Zhang; Siqi Wang; Zhiwei Li; Raymond R. Tan; Fang Wang; Xiaoping Jia (Journal of Cleaner Production, 2025)

Laodelphax striatellus salivary sheath protein Lsactin triggers defense response in plants - Liangxuan Qi; Jing Li; Han Wang; Jing Li; Xinyang Tan; Zhichang Zhao; Sicong Zhou; Jichao Fang; Rui Ji (Insect Biochemistry and Molecular Biology, 2025)

Antibiotic-induced multi-trophic effects and their cascades in a sub-tropical freshwater ecosystem - Kai-Sheng Yao; Pei-Liang Zhou; Li-Juan Tan; Hua-Qiao Yang; Lu-Kai Qiao; Fang-Zhou Gao; You-Sheng Liu; Feng-Jiao Peng; Guang-Guo Ying; Paul J. Van den Brink (Journal of Hazardous Materials, 2025)

Screening novel anti-inflammatory peptides inhibiting the NLRP3 inflammasome from UHPLC-MS/MS-characterized peptide profiles of cocoa tea protein hydrolysates - Hai-Biao Gong; Chang-Yu Yan; Hui-Er Ye; Shuo-Yan Tan; Shi-Sheng Chen; Jian-Wen Ye; Wan-Yang Sun; Hong-Li Tan; Xiang Luo; Jie Niu; Kun Li; Jing-Hao Wang; et al. (Food Research International, 2025)

Genomic analysis of the novel Stenotrophomonas phage vB_Srh_LBjhp91a, isolated from a Karst cave in China - Lou Ren; Zheng Fang; Shixia Li; Qingshan Wu; Lan Xiang; Chuangen Lin; Qiuping Liu; Leitao Tan; Qingbei Weng (Archives of Virology, 2025)

Study on macro- and sporemorphology of a new species of Coniopteris (Dicksoniaceae) from the Middle Jurassic of western Liaoning, Northeast China - Fang-Yu Li; Xiao Tan; Yun-Yan Xiu; Wen-Tao Liu; Meng-Yu Chen; Ning Tian (Review of Palaeobotany and Palynology, 2025)

Optimizing boron oxide-support interactions for enhanced catalytic stability in propane oxidative dehydrogenation - Jinshu Tian; Kerou Hu; Ling Fang; Chi Wang; Ru Kong; Mingwu Tan; Lili Zhang; Zhongting Hu; Xiaonian Li; Yihan Zhu (Chemical Engineering Journal, 2025)

QTL mapping and multi-omics identify candidate genes for protein and oil in soybean - Xiaomei Fang; Jiaqi Liu; Aohua Jiang; Xi Li; Pingting Tan; Chen Liu; Xuan Gong; Hao Sun; Chengzhang Du; Jijun Zhang; Xiaochun Zhang; Zelin Yi; et al. (Theoretical and Applied Genetics, 2025)

Study of D s 1 ( 2460 ) + → D s + π + π - in B → D ‾ ( * ) D s + π + π - decays - R. Aaij; A.S.W. Abdelmotteleb; C.Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2025)

Research on combustion characteristics of new high energy composite materials − using tungsten powder as fuel and DAP-4 as oxidizer - Guangwei Xiao; Erhai An; Hua Fang; Xueli Zhang; Yingxin Tan; Lin Li; Peng Deng; Zhuoxin Fei; Xiong Cao (Fuel, 2025)

Specifically targeted antimicrobial cyclic peptide to staphylococcal protein A for the treatment of S. aureus infection - Xiao-Ling Lei; Yong Li; Xue-Ting Cheng; Jie Zhuang; Fang Zhang; Xiao-Ting Xie; Lin-Fang Tan; Jin-Xuan Fan; Yuan-Di Zhao; Chuan-Liu Wu; Kai Cheng (Chemical Engineering Journal, 2025)

Three new metabolites from the endophyte Fusarium proliferatum T2-10 - Jian-Bing Tan; Wei-Wei Peng; Mei-Fang Li; Feng-Hua Kang; Yu-Ting Zheng; Li Xu; Si-Yu Qin; Yuan-Tao Huang; Zhen-Xing Zou (Natural Product Research, 2025)

Qualities and bitter substances profile of Chinese winter jujube (Ziziphus jujuba Mill. cv. Dong zao) under the ultra-low oxygen environment - Xiaoxue Li; Xiaomei Zhao; Shaojin Wang; Bin Wu; Yuxing Du; Chenghu Dong; Zhonghong Wu; Fang Sun; Jiahui Wu; Li Wang; Ning Liu; Boya Zhang; et al. (Postharvest Biology and Technology, 2025)

The combined microplastics and heavy metals contamination between the soil and aquatic media: A review - Yifan Zhang; Dan Li; Kunlong Hui; Hui Wang; Ying Yuan; Fei Fang; Yu Jiang; Beidou Xi; Wenbing Tan (Journal of Environmental Chemical Engineering, 2025)

Role of per- and polyfluoroalkyl substances in the cardiorenal system: Unraveling crosstalk from the network of pollutants and phenotypes - Ming Yang; Jiaxin Zhao; Ziwen An; Haoran Li; Chaoying Ma; Junli Lv; Fang Xiao; Zhenzhen Tan; Longfei Li; Xiaoguang Zhang; Xuehui Liu; Yi Liu; et al. (Journal of Environmental Sciences, 2025)

Microseisms at the Gakkel Ridge, Arctic Ocean: Results from the JASMInE ocean bottom seismic experiment - Zhangju Liu; Jiabiao Li; Fansheng Kong; Xiongwei Niu; Weiwei Ding; Tao Zhang; Pingchuan Tan; Yulong Zhou; Mei Xue; Yinxia Fang (Science China Earth Sciences, 2025)
To characterize mid-ocean microseisms in the Arctic Ocean and explore potential seismic ambient noise imprint of Arctic warming, this study analyzes seismic records from nine ocean bottom seismometers (OBSs) deployed along the eastern Gakkel Ridge during the Joint Arctic Scientific Middle-ocean ridge Insight Expedition (JASMInE) in August 2021. In the period band of single frequency microseisms (10–20 s), typically produced by ocean waves directly impacting coastlines, no prominent spectral peaks are observed. In the double frequency microseism (DFM) period band (2–10 s), spectral powers are far less energetic than those in the open oceans by approximately 20–40 dB, especially for OBSs deployed off the Gakkel Ridge axis. This dramatically weak DFMs can be attributed to the presence of the perennial sea-ice cover, which hinders atmosphere-ocean interactions and thus obstructs the generation of DFMs. Based on polarization analyses of Rayleigh waves and correlations of DFM power and ocean wave height, the weak DFMs recorded on the seafloor likely originate from the northern Barents Sea and adjacent regions. As an Arctic warming hotspot, the northern Barents Sea is experiencing reduced sea-ice import from the interior Arctic which enhances atmosphere-ocean interactions. In this region, wind-driven waves with highly variable directions as documented by oceanographic data and the presence of the perennial sea-ice cover may promote the formation of wave trains propagating in nearly opposite directions, which nonlinear interactions excite DFMs. These DFMs continuously lose power due to seismic attenuation during propagation, becoming so weak that the OBSs deployed off the ridge axis detect no noticeable spectral peaks in the DFM period band. The OBSs along the ridge axis, by contrast, reveal more energetic power in the short-period DFM band of 2–5 s, which can be attributed to local DFM amplification caused by the thick unconsolidated sediment layer.

Real-time detection of hypoxic stress behavior in aquaculture fish using an enhanced YOLOv8 model - Chengqing Cai; Shuangyi Tan; Xinmiao Wang; Bohao Zhang; Chaowei Fang; Guanbin Li; Longqin Xu; Shuangyin Liu; Ruixin Wang (Aquaculture International, 2025)

Chronic intermittent hypoxia modulates energy metabolic pathways and improves hypoxia tolerance capacity in golden pompano, Trachinotus blochii - Geng Hui Fang; Xiao Li Zhou; Chun Li Ran; Chun Xiu Jin; Shao Yang Bu; Yue Chen; Yong Gong; Zeng Tan Hu; Fei Biao Song; Jian Luo; Jun Long Sun (Science of The Total Environment, 2025)

The inhibition mechanism of N2O generation in NH3-SCR process by water vapor - Junchen Li; Cheng Zhang; Dingli Fang; Zhao Zheng; Yan Zhao; Peng Tan; Qingyan Fang; Gang Chen (Journal of Hazardous Materials, 2025)

Long-term effectiveness of heavy metal(loid) stabilization: Development of an assessing method - Yanqing Liu; Zewen Wang; Xiao Tan; Deyi Hou; Liping Fang; Aijun Lin; Fangbai Li; Guilan Duan (Environmental Pollution, 2025)

Tissue accumulation and hepatotoxicity of 8:2 chlorinated polyfluoroalkyl ether sulfonate: A multi-omics analysis deciphering hepatic amino acid metabolic dysregulation in mice - Zhenzhen Tan; Ziwen An; Junli Lv; Fang Xiao; Longfei Li; Jing Li; Wenjing Duan; Mingmei Guo; Xiuli Zeng; Yi Liu; Ang Li; Huicai Guo (Journal of Hazardous Materials, 2025)

Super-fast and highly efficient extraction of uranium from water by a surface-acidified hydroxyapatite - Jiayi Li; Yuxin Liu; Zihao Ye; Hangxi Liu; Xiaoli Tan; Ming Fang (Journal of Environmental Chemical Engineering, 2025)

Lipid peroxidation inhibition by icaritin and its glycosides as a strategy to combat iron overload-induced osteoporosis in zebrafish - Chang-Yu Yan; Xiao-Yuan Gu; Shuo-Yan Tan; Ao-Yu Mei; Jiang-Hao Mao; Yi Dai; Jie Niu; Wei-Xi Li; Hiroshi Kurihara; Yi-Fang Li; Rong-Rong He (Food Research International, 2025)

Effects of dimethylarsenate coprecipitation with ferrihydrite on Fe(II)-induced mineral transformation and the release of dimethylarsenate - Yi Chen; Yueyang Quan; Yipu Liu; Meng Yuan; Jiaqi Wang; Chuan Chen; Chuanqin Huang; Xiaoyu Fang; Jing Zhang; Xionghan Feng; Wenfeng Tan; Jiangshan Li; et al. (Environmental Pollution, 2025)

The role of phenology in crop yield prediction: Comparison of ground-based phenology and remotely sensed phenology - Jie Pei; Shaofeng Tan; Yaopeng Zou; Chunhua Liao; Yinan He; Jian Wang; Huabing Huang; Tianxing Wang; Haifeng Tian; Huajun Fang; Li Wang; Jianxi Huang (Agricultural and Forest Meteorology, 2025)

Performance prediction of urban tunnel purification system based on the verified random number screening algorithm - Jie Xia; Hao-Yi Zhao; Hui Ren; Long Chen; Fang Li; Wei-Rong Shi; Yi-Song Xie; Mei-Lan Tan; Fei Li; Bin Zhou (Sustainable Cities and Society, 2025)

Dynamic trends in maize diseases and pests across six regions in China over two decades - Hong-ying Cui; Amber Sciligo; Xiao-ling Tan; Cang Hui; Yong-sheng Zhang; Wei Li; Zi-qiao Zhou; Zhen-qing Peng; Ping Ma; Zhi-shu Xiao; Fang Ouyang (Crop Protection, 2024)

Efficient removal of aqueous ciprofloxacin antibiotic by ZnO/CuO-bentonite composites synthesized via carbon-bed pyrolysis of bentonite and metal co-precipitation - Xiaodong Yang; Xuefei Yang; Zhiyong Hou; Minghui Li; Shuaiqi Luo; Jin Zhao; Kai Wang; Yuanxia Guo; Pengkai Sun; Fang Tan; Yan Yan; Lulu Liu; et al. (Science of The Total Environment, 2024)

Understanding the synergistic catalysis of balanced Cu0-Cu+ sites and oxygen vacancies in Cu/ZrO2 catalysts for the efficient hydrogenation of furfural - Xinling Yang; Zhou Chen; Jingjing Tan; Yuanna Zhang; Jinglei Cui; Changzhen Wang; Li Fang; Yulei Zhu; Long Huang; Hu Shi; Yongzhao Wang (Chemical Engineering Journal, 2024)

Establishment of a semi-continuous scale-down clone screening model for intensified perfusion culture - Tao Sun; Yu Zhang; Hengrui Liang; Wenjing Fang; Zichen Qian; Kee Wee Tan; Junjie Li; Xiang Zheng; Mingyue Fang; Hang Zhou; Weichang Zhou; Sam Zhang (Biotechnology Letters, 2024)

Metagenomic insights into the mechanistic differences of plant polyphenols and nitrocompounds in reducing methane emissions using the rumen simulation technique - Jian Tan; Ying Wang; Haoyu Niu; Liuxue Li; Huiying Zhao; Luoyun Fang; Linshu Jiang; Yuchao Zhao (Science of The Total Environment, 2024)

Distribution mechanisms of soil surface erosion and underground leakage in karst areas of China: A systematic, quantitative review - Jia Chen; Pingping Fan; Feng Zhang; Tingjun Tan; Nufang Fang; Zeyan Wu; Zhongwu Li; Yaojun Liu (CATENA, 2024)

Identification of key anthropogenic and land use factors and ecological risk assessment of dissolved polycyclic aromatic hydrocarbons (PAHs) and organochlorine pesticides (OCPs) in an urbanized estuary in China - Huijun Liu; Jiajie Hu; Yan Tan; Zhong Zheng; Mengyang Liu; Rainer Lohmann; Simon Vojta; Samuel Katz; Yong Liu; Zhiheng Li; Zhiguo Fang; Minggang Cai; et al. (Marine Pollution Bulletin, 2024)

Nano-enabled strategies to promote safe crop production in heavy metal(loid)-contaminated soil - Li Chen; Linchuan Fang; Wenfeng Tan; Haijian Bing; Yi Zeng; Xunfeng Chen; Zimin Li; Weifang Hu; Xing Yang; Sabry M. Shaheen; Jason C. White; Baoshan Xing (Science of The Total Environment, 2024)

Preparation and characterization of Ti3C2 Mxene through back propagation neural network-genetic algorithm combined with surface method response - Wei Wang; Mingrong Lu; Shuju Fang; Guizhen Li; Jianjun Wang; Xuewen Tan (Process Safety and Environmental Protection, 2024)

RAD-seq data for Engelhardia roxburghiana provide insights into the palaeogeography of Hainan Island and its relationship to mainland China since the late Eocene - Pei-Han Huang; Tian-Rui Wang; Min Li; Zi-Jia Lu; Ren-Ping Su; Ou-Yan Fang; Lang Li; Shi-Shun Zhou; Yun-Hong Tan; Hong-Hu Meng; Yi-Gang Song; Jie Li (Palaeogeography, Palaeoclimatology, Palaeoecology, 2024)

A superstructure-based model for the evolution of park-wide water infrastructure - Zhiwei Li; Ziting Ge; Chao Wang; Dawei Zhang; Jianghai Dou; Raymond R. Tan; Fang Wang; Xiaoping Jia (Journal of Cleaner Production, 2024)

The potential of magnetic biochar prepared by a solvent-free method as a soil amendment: Metal immobilization performance, soil microbial co-occurrence network and community assembly mechanism - Jiacan Li; Yucan Sun; Mingzhi Fang; Zizhang Guo; Bing Zhang; Tan Chen; Yifei Liu; Ting Yang; Linlan Zhuang (Journal of Environmental Chemical Engineering, 2024)

Highly acid-stable polyvinyl alcohol/chitosan/phytic acid aerogel for selective separation of uranium from actual wastewater - Xiaoyan Wu; Qiuyang Tang; Xiaowen Zhang; Qi Fang; Yilong Hua; Tao Cai; Wei Tan; Jie Kou; Ziyin Wang; Mengge Tian; Jiayi Qu; Mi Li (Journal of Environmental Chemical Engineering, 2024)

Effects of municipal solid waste component on gasification performance and chromium partitioning behavior under CO2 atmosphere - Yan Zhao; Cheng Zhang; Lun Ma; Junchen Li; Zhao Zheng; Peng Tan; Qingyan Fang; Gang Chen (Chemical Engineering Journal, 2024)

Inflammatory microenvironment-responsive “double-insurance” nanoreactors for accurate sonodynamic-chemodynamic therapy of rheumatoid arthritis - Sui Zhou; Meng-Wen Ma; Shao-Zhe Cai; Kai-Lin He; Lin-Fang Tan; Kai Cheng; Jin-Xuan Fan; Ling-Li Dong; Bo Liu (Chemical Engineering Journal, 2024)

Hybrid molecularly imprinted polymers for targeted separation and enrichment of 10-hydroxycamptothecin in Camptotheca acuminata Decne - Yanwei Xu; Yulian Tan; Zahid Majeed; Fang Nie; Kaili Zheng; Zhonghao Li; Lian Yang; Chunjian Zhao; Chunying Li (Natural Product Research, 2024)

A fluorimetric and colorimetric dual-mode sensor based on N, S co-doped carbon dots functionalized silver nanoparticles for glucose detection - Shuju Fang; Shaoqing Li; Pengyuan Yin; Guixiang Yao; Hang Yu; Yanzhi He; Xiaopei Li; Min Yang; Wei Tan (Chemosphere, 2024)

Inverting continuous in-tunnel passive seismic data for velocity structure mapping ahead of the TBM cutterhead - Enhedelihai Alex Nilot; Yunyue Elita Li; Gang Fang; Yun Zhou Tan; Arthur Cheng (Tunnelling and Underground Space Technology, 2024)

An activatable fluorescence probe for rapid detection and in situ imaging of β-galactosidase activity in cabbage roots under heavy metal stress - Kuicheng Zhao; Hongli Tan; Cong Fang; Zile Zhou; Cuiyan Wu; Xiaohua Zhu; Feng Liu; Youyu Zhang; Haitao Li (Food Chemistry, 2024)

Microwave-assisted preparation of yellow fluorescent graphitic carbon nitride quantum dots for trace tetracycline-specific detection - Yanzhi He; Xiaopei Li; Guixiang Yao; Shuju Fang; Hang Yu; Tianru Zou; Wei Tan; Hongbin Wang (Chemosphere, 2024)

Efficient catalytic oxidation of formaldehyde by defective g–C3N4–anchored single-atom Pt: A DFT study - Zhao Zheng; Cheng Zhang; Junchen Li; Dingli Fang; Peng Tan; Qingyan Fang; Gang Chen (Chemosphere, 2024)

Conditions optimization and mechanistic study of chlortetracycline hydrochloride adsorption by TBAOH-MXene: Prediction results based on backpropagation neural network-genetic algorithm and response surface methodology - Mingrong Lu; Shuju Fang; Yao Zhang; Hongyang Zheng; Honglin Xie; Chunxian Zhou; Xuewen Tan; Wanqin Wu; Guizhen Li (Process Safety and Environmental Protection, 2024)

Comparative study of organic removal by pre-adsorption oxidation and synchronous adsorption oxidation processes: Performance and mechanism - Bo Tan; Ge Gou; Yi Ren; Zhuoyao Fang; Chao Liu; Bo Lai; Naiwen Li; Jun Li (Journal of Hazardous Materials, 2024)

Insight into the effect of exposed crystal facets of anatase TiO2 on HCHO catalytic oxidation of Mn-Ce/TiO2 - Zhao Zheng; Cheng Zhang; Junchen Li; Dingli Fang; Peng Tan; Qingyan Fang; Gang Chen (Journal of Hazardous Materials, 2024)

Single-/Co-Driving of Tetracycline, Triclocarban and Zinc on Microbial Community, Resistome and Function in the Cyanobacteria-Blooming Freshwater Ecosystem - Fang-Zhou Gao; Kai-Sheng Yao; Li-Juan Tan; Liang-Ying He; You-Sheng Liu; Guang-Guo Ying (Bulletin of Environmental Contamination and Toxicology, 2024)

Glutathione-activated biotin-targeted dual-modal imaging probe with improved PDT/PTT synergistic therapy - Zhi-Chao Yang; Qing-Song Gu; Jing-Jing Chao; Fang-Yuan Tan; Guo-Jiang Mao; Liufang Hu; Juan Ouyang; Chun-Yan Li (Analytica Chimica Acta, 2024)

Regional uncertainty analysis between crop phenology model structures and optimal parameters - Chenyao Yang; Na Lei; Christoph Menz; Andrej Ceglar; Jairo Arturo Torres-Matallana; Siqi Li; Yanling Jiang; Xianming Tan; Lei Tao; Fang He; Shigui Li; Bing Liu; et al. (Agricultural and Forest Meteorology, 2024)

Construction of blackberry polysaccharide nano-selenium particles: Structure features and regulation effects of glucose/lipid metabolism in HepG2 cells - Dou Zu-Man; Zhang Yu-Long; Tang Chun-Yang; Liu Chuang; Fang Jia-Qin; Huang Qiang; Chen Chun; You Li-Jun; Tan Chin-Ping; Niu Hui; Fu Xiong (Food Research International, 2024)

Catalytic oxidation of formaldehyde by MnOx-decorated anatase TiO2{001}: Investigation of the effect of calcination temperature on catalytic activity and reaction mechanism - Zhao Zheng; Cheng Zhang; Junchen Li; Yan Zhao; Dingli Fang; Ao Han; Peng Tan; Qingyan Fang; Gang Chen (Journal of Environmental Chemical Engineering, 2024)

Phase development in steelmaking slags during a gas quenching granulation process - Wen-Feng Gu; Jiang Diao; Li-Yuan Jiang; Hua-Fang Yu; Wen-Feng Tan; Lian Chen; Hong-Yi Li; Bing Xie; Shigeru Ueda (Journal of Environmental Chemical Engineering, 2024)

An in-depth revelation of a novel facilitation mechanism of H2O on the NH3-SCR reaction of Mn-Ce/TiO2 catalyst with exposed anatase {001} facets - Junchen Li; Cheng Zhang; Dingli Fang; Zhao Zheng; Yan Zhao; Peng Tan; Qingyan Fang; Gang Chen (Fuel, 2024)

Fully automated measurement of femoral neck axis line in anatomical coordinate system using CT images - Li Li; Qiyao Ye; Tan Hu; Dongshen Fang; Runyu Wan; Yu Shi (Medical & Biological Engineering & Computing, 2024)

COVID-19 in Systemic Lupus Erythematosus patients treated with belimumab: a retrospective clinical study - Yinlan Wu; Yanhong Li; Tong Wu; Deying Huang; Jianhong Wu; Weihua Zhang; Xuejun Jiang; Chaoqiong Yao; Xiuping Liang; Lu Cheng; Zehui Liao; Fang Xu; et al. (Immunologic Research, 2024)

Characteristics and whole-genome analysis of a novel Pseudomonas syringae pv. tomato bacteriophage D6 isolated from a karst cave - Qingshan Wu; Ni An; Zheng Fang; Shixia Li; Lan Xiang; Qiuping Liu; Leitao Tan; Qingbei Weng (Virus Genes, 2024)
Pseudomonas syringae is a gram-negative plant pathogen that infects plants such as tomato and poses a threat to global crop production. In this study, a novel lytic phage infecting P. syringae pv. tomato DC3000, named phage D6, was isolated and characterized from sediments in a karst cave. The latent period of phage D6 was found to be 60 min, with a burst size of 16 plaque-forming units per cell. Phage D6 was stable at temperatures between 4 and 40 °C but lost infectivity when heated to 70 °C. Its infectivity was unaffected at pH 6–10 but became inactivated at pH ≤ 5 or ≥ 12. The genome of phage D6 is a linear double-stranded DNA of 307,402 bp with a G + C content of 48.43%. There is a codon preference between phage D6 and its host, and the translation of phage D6 gene may not be entirely dependent on the tRNA library provided by the host. A total of 410 open reading frames (ORFs) and 14 tRNAs were predicted in its genome, with 92 ORFs encoding proteins with predicted functions. Phage D6 showed low genomic similarity to known phage genomes in the GenBank and Viral sequence databases. Genomic and phylogenetic analyses revealed that phage D6 is a novel phage. The tomato plants were first injected with phage D6, and subsequently with Pst DC3000, using the foliar spraying and root drenching inoculum approach. Results obtained after 14 days indicated that phage D6 inoculation decreased P. syringae- induced symptoms in tomato leaves and inhibited the pathogen’s growth in the leaves. The amount of Pst DC3000 was reduced by 150- and 263-fold, respectively. In conclusion, the lytic phage D6 identified in this study belongs to a novel phage within the Caudoviricetes class and has potential for use in biological control of plant diseases.

Recent advances in developing butyrogenic functional foods to promote gut health - Miao Zhang; Robert W. Li; Haiyan Yang; Zhongfang Tan; Fang Liu (Critical Reviews in Food Science and Nutrition, 2024)

Density functional theory-based screening of Ti4C3O2-loaded single atoms for efficient selective catalytic oxidation of formaldehyde - Zhao Zheng; Cheng Zhang; Junchen Li; Dingli Fang; Peng Tan; Qingyan Fang; Gang Chen (Chemosphere, 2024)

Prediction of soil organic carbon in black soil based on a synergistic scheme from hyperspectral data: Combining fractional-order derivatives and three-dimensional spectral indices - Jing Geng; Junwei Lv; Jie Pei; Chunhua Liao; Qiuyuan Tan; Tianxing Wang; Huajun Fang; Li Wang (Computers and Electronics in Agriculture, 2024)

Quantifying tunneling risks ahead of TBM using Bayesian inference on continuous seismic data - Gang Fang; Enhedelihai Alex Nilot; Yunyue Elita Li; Yun Zhou Tan; Arthur Cheng (Tunnelling and Underground Space Technology, 2024)

Vulnerability optimization for determining water restoration strategies in industrial park water networks - Yanmei Zhang; Chenxuan Wang; Jianghai Dou; Zhiwei Li; Peidong Zhang; Raymond R. Tan; Fang Wang; Xiaoping Jia (Resources, Conservation and Recycling, 2024)

Comprehensive effect of increased calcium content in coal on the selenium emission from coal-fired power plants: Combined laboratory and field experiments - Yan Zhao; Cheng Zhang; Lun Ma; Shenghui Yu; Junchen Li; Peng Tan; Qingyan Fang; Guangqian Luo; Hong Yao; Gang Chen (Journal of Hazardous Materials, 2024)

Moisture actuated cobalt alginate discoloration artificial muscle - Chenxue Xiang; Wen Wang; Henry Ming Wang; Yangjie Huang; Lele zhang; Shuting Fang; Hao Tan; Mufang Li; Dong Wang (Chemical Engineering Journal, 2024)

Pseudocercones A-C, three new polyketide derivatives from the endophytic fungus Pseudocercospora sp. TSS-1 - Wei-Wei Peng; Min Kuang; Yuan-Tao Huang; Mei-Fang Li; Yu-Ting Zheng; Li Xu; Jian-Bing Tan; Feng-Hua Kang; Hai-Bo Tan; Zhen-Xing Zou (Natural Product Research, 2024)

Examining diverse remediation mechanisms of biochar in soil contaminated with polycyclic aromatic hydrocarbon (PAH) of various ring structures: A global meta-analysis - Qingzi Li; Renjie Chen; Yun Xu; Chang Chen; Juan Xiong; Wenfeng Tan; Linchuan Fang (Science of The Total Environment, 2024)

Multi-objective optimization of straw-based bio-natural gas supply chains considering cost, CO2 emission, and safety - Tianyuan Zhou; Taomeizi Zhou; Zhiwei Li; Kathleen B. Aviso; Raymond R. Tan; Xiaoping Jia; Fang Wang (Journal of Cleaner Production, 2024)

Integrated decision-making approach for sectoral low-carbon technology solutions - Taomeizi Zhou; Zhiwei Li; Xiaoping Jia; Kathleen B. Aviso; Raymond R. Tan; Xuexiu Jia; Fang Wang (Journal of Cleaner Production, 2024)

Flexural performance of a prefabricated steel–UHPC composite deck under transverse hogging moment - Xingyu Tan; Zhi Fang; Xiaonan Wu; Xiukun Li; Yuan Liao; Shan Pei (Engineering Structures, 2024)

IiAGL6 participates in the regulation of stamen development and pollen formation in Isatis indigotica - Liu Yang; Xin Qiao; Hao-En He; Wei-Wei Yi; Ya-Nan Gao; Xiao-Min Tan; Hao Cheng; Xiao-Fang Hou; Ye-Ye Ma; Hong-Li Wang; Xuan Huang; Yan-Qin Ma; et al. (Plant Science, 2024)

Ozone exposure affects corneal epithelial fate by promoting mtDNA leakage and cGAS/STING activation - Kai Fan; Nuo Dong; Meichai Fang; Zixun Xiang; Lan Zheng; Mengyuan Wang; Yukuan Shi; Gang Tan; Cheng Li; Yuhua Xue (Journal of Hazardous Materials, 2024)

Modeling of arsenic migration and emission characteristics in coal-fired power plants - Yan Zhao; Cheng Zhang; Lun Ma; Shenghui Yu; Changle Yuan; Junchen Li; Peng Tan; Qingyan Fang; Guangqian Luo; Gang Chen (Journal of Hazardous Materials, 2024)

Bioaccessibility of docosahexaenoic acid in naturally and artificially enriched milk - Pengjie Wang; Panqiao Chen; Xiaoxu Zhang; Ignatius Man-Yau Szeto; Fang Li; Shengjie Tan; Genna Ba; Yan Zhang; Sufang Duan; Yue Yang (Food Chemistry, 2024)

The structural and functional properties of a novel enzyme-modified starch as an alternative to hydroxypropyl starch ether - Ruobing Li; Haiteng Tao; Congping Tan; Fang Yuan; Li Guo; Bo Cui; Yu Zhu; Feixue Zou; Pengfei Liu; Lu Lu (Food Hydrocolloids, 2024)

Effect of different screw speeds on the structure and properties of starch straws - Kun Wang; Congping Tan; Haiteng Tao; Fang Yuan; Li Guo; Bo Cui (Carbohydrate Polymers, 2024)

Insights into the long-term immobilization performances and mechanisms of CMC-Fe0/FeS with different sulfur sources for uranium under anoxic and oxic aging - Qi Fang; Yanling Tan; Ran Yan; De Zhang; Mi Li; Xiaoyan Wu; Yilong Hua; Wenjing Xue; Rongzhong Wang (Journal of Environmental Management, 2024)

Copper peroxide and cisplatin co-loaded silica nanoparticles-based trinity strategy for cooperative cuproptosis/chemo/chemodynamic cancer therapy - Xuelian He; Meijing Li; Sijun Fan; Yuying Li; Lei Fang; Guangya Xiang; Tan Yang (Chemical Engineering Journal, 2024)

Effects of temperature on the migration behaviour of arsenic and chromium in tannery sludge under CO2 gasification - Yan Zhao; Cheng Zhang; Lun Ma; Junchen Li; Peng Tan; Qingyan Fang; Gang Chen (Journal of Hazardous Materials, 2024)

Optimizing nitrogen application rate by establishing a unified critical nitrogen dilution curve for maize under different mulching planting patterns - Wenlong Li; Xiaobo Gu; Heng Fang; Tongtong Zhao; Rui Yin; Zhikai Cheng; Chuandong Tan; Zhihui Zhou; Yadan Du (European Journal of Agronomy, 2024)

The responses of soil Cd fractions to disinfestation regimes associated with microbial communities - Xin Li; Yu Tao; Fang Chen; Fangjun Tan; Chi Zhou; Jie Chen; Tao Xue; Yunhe Xie (Applied Soil Ecology, 2024)

Deciphering microbiomes dozens of meters under our feet and their edaphoclimatic and spatial drivers - Haoran He; Jingxiong Zhou; Yunqiang Wang; Shuo Jiao; Xun Qian; Yurong Liu; Ji Liu; Ji Chen; Manuel Delgado‐Baquerizo; Albert C. Brangarí; Li Chen; Yongxing Cui; et al. (Global Change Biology, 2024)
Microbes inhabiting deep soil layers are known to be different from their counterpart in topsoil yet remain under investigation in terms of their structure, function, and how their diversity is shaped. The microbiome of deep soils (>1 m) is expected to be relatively stable and highly independent from climatic conditions. Much less is known, however, on how these microbial communities vary along climate gradients. Here, we used amplicon sequencing to investigate bacteria, archaea, and fungi along fifteen 18‐m depth profiles at 20–50‐cm intervals across contrasting aridity conditions in semi‐arid forest ecosystems of China's Loess Plateau. Our results showed that bacterial and fungal α diversity and bacterial and archaeal community similarity declined dramatically in topsoil and remained relatively stable in deep soil. Nevertheless, deep soil microbiome still showed the functional potential of N cycling, plant‐derived organic matter degradation, resource exchange, and water coordination. The deep soil microbiome had closer taxa–taxa and bacteria–fungi associations and more influence of dispersal limitation than topsoil microbiome. Geographic distance was more influential in deep soil bacteria and archaea than in topsoil. We further showed that aridity was negatively correlated with deep‐soil archaeal and fungal richness, archaeal community similarity, relative abundance of plant saprotroph, and bacteria–fungi associations, but increased the relative abundance of aerobic ammonia oxidation, manganese oxidation, and arbuscular mycorrhizal in the deep soils. Root depth, complexity, soil volumetric moisture, and clay play bridging roles in the indirect effects of aridity on microbes in deep soils. Our work indicates that, even microbial communities and nutrient cycling in deep soil are susceptible to changes in water availability, with consequences for understanding the sustainability of dryland ecosystems and the whole‐soil in response to aridification. Moreover, we propose that neglecting soil depth may underestimate the role of soil moisture in dryland ecosystems under future climate scenarios.

Surveillance of COVID-19 and influenza A(H1N1) prevalence in China via medicine-based wastewater biomarkers - Xue-Ting Shao; Yan-Song Wang; Zhen-Fang Gong; Yan-Ying Li; Dong-Qin Tan; Jian-Guo Lin; Wei Pei; De-Gao Wang (Water Research, 2023)

Effects of polyols with different hydroxyl numbers on the structure and properties of starch straws - Chenyu Ma; Haiteng Tao; Congping Tan; Shijun Gao; Zehua Wu; Li Guo; Bo Cui; Fang Yuan; Feixue Zou; Pengfei Liu; Lu Lu (Carbohydrate Polymers, 2023)

Effect of cage culture on sedimentary heavy metal and water nutrient pollution: Case study in Sansha Bay, China - Yan Song; Maotian Li; Yixuan Fang; Xiaoqiang Liu; Huikun Yao; Chun Fan; Zijie Tan; Yan Liu; Jing Chen (Science of The Total Environment, 2023)

Ecytonucleospora hepatopenaei n. gen. et comb. (Microsporidia: Enterocytozoonidae): A redescription of the Enterocytozoon hepatopenaei (Tourtip et al., 2009), a microsporidian infecting the widely cultivated shrimp Penaeus vannamei - Yuan Wang; Jie Chen; Ying Na; Xin-cang Li; Jun-fang Zhou; Wen-hong Fang; Hong-xin Tan (Journal of Invertebrate Pathology, 2023)

Lithospheric velocity structure of South China Sea basin from ocean bottom seismometer ambient noise tomography - Liqun Cheng; Yinxia Fang; Xiongwei Niu; Tingzi Li; Chongzhi Dong; Yanghui Zhao; Hao Hu; Fansheng Kong; Pingchuan Tan; Aiguo Ruan; Shaoping Lu; Jianke Fan; et al. (Tectonophysics, 2023)

One-pot preparation of bi-functional POSS-based hybrid monolith via photo-initiated polymerization for isolation of extracellular vesicles - Qi Zhang; Mengxi Chen; Fang Xu; Wen Wu; Xintong Luo; Ying Wang; Jiaxi Li; Xuanhao Cui; Yujia Tan; Zhi Li; Yujie Lin; Haiyang Zhang; et al. (Analytica Chimica Acta, 2023)

Facet-dependent U(VI) removal of hematite with confined ferrous ions - Jing Zhang; Shuya Liu; Zhimin Lv; Yuxin Liu; Feixue Gao; Kexin Li; Xiaoli Tan; Xiushen Ye; Ming Fang (Environmental Science and Pollution Research, 2023)

Optimization of adsorption performance of cerium-loaded intercalated bentonite by CCD-RSM and GA-BPNN and its application in simultaneous removal of phosphorus and ammonia nitrogen - Mingrong Lu; Shuju Fang; Guizhen Li; Wei Wang; Xuewen Tan; Wanqin Wu (Chemosphere, 2023)

Real-time tunneling risk forecasting using vibrations from the working TBM - Enhedelihai Alex Nilot; Gang Fang; Yunyue Elita Li; Yun Zhou Tan; Arthur Cheng (Tunnelling and Underground Space Technology, 2023)

The new records of Coniopteris (Dicksoniaceae, Filicales) with in-situ spores from the Middle Jurassic of northeastern China and its spatio-temporal distribution in China - Fang-Yu Li; Yun-Yan Xiu; Xiao Tan; Ning Tian (Review of Palaeobotany and Palynology, 2023)

mTORC1/rpS6 and mTORC2/PKC regulate spermatogenesis through Arp3-mediated actin microfilament organization in Eriocheir sinensis - Zhen-Fang Li; Hong-Yu Qi; Jia-Ming Wang; Zhan Zhao; Fu-Qing Tan; Wan-Xi Yang (Cell and Tissue Research, 2023)

A colorimetric and fluorometric dual-mode probe for Cu2+detection based on functionalized silver nanoparticles - Guixiang Yao; Shuju Fang; Pengyuan Yin; Ailing Li; Wenrong Yang; Hongbin Wang; Wei Tan (Environmental Science and Pollution Research, 2023)

Safety risk assessment of the large-scale carbon capture, utilization, and storage demonstration project in Dongying, China - Fang Wang; Jinkang Cao; Yanmei Zhang; Kathleen B. Aviso; Raymond R. Tan; Zhiwei Li; Xiaoping Jia (Journal of Cleaner Production, 2023)

TiO2 nanoparticles affect spermatogenesis and adhesion junctions via the ROS-mediated mTOR signalling pathway in Eriocheir sinensis testes - Lan-Min Wang; Ke Jia; Zhen-Fang Li; Hong-Yu Qi; Ding-Xi Liu; Ya-Jing Liang; Shuang-Li Hao; Fu-Qing Tan; Wan-Xi Yang (Environmental Pollution, 2023)

Spatiotemporal dynamics of near-surface ozone concentration and potential source areas in northern China during 2015—2020 - Kang Ma; Yuesheng Lin; Fengman Fang; Huarong Tan; Jingwen Li; Lei Ge; Fei Wang; Youru Yao (Environmental Science and Pollution Research, 2023)

The PIWI-specific insertion module helps load longer piRNAs for translational activation essential for male fertility - Xin Wang; Di-Hang Lin; Yue Yan; An-Hui Wang; Jiaoyang Liao; Qian Meng; Wen-Qing Yang; Heng Zuo; Min-Min Hua; Fengjuan Zhang; Hongwen Zhu; Hu Zhou; et al. (Science China Life Sciences, 2023)

Norgestrel causes digestive gland injury in the clam Mactra veneriformis: An integrated histological, transcriptomics, and metabolomics study - Xiaoran Zhao; Qing Wang; Xiangfei Li; Hua Xu; Chuanbo Ren; Yanyan Yang; Shuhao Xu; Guoxing Wei; Yujun Duan; Zhitao Tan; Yan Fang (Science of The Total Environment, 2023)

Effects of various thermal treatments on interfacial composition and physical properties of bovine milk fat globules - Yingchao Huang; Teng Wei; Fang Chen; Chaoli Tan; Zhiqing Gong; Fengxin Wang; Zeyuan Deng; Jing Li (Food Research International, 2023)

The mechanism of promoting rhizosphere nutrient turnover for arbuscular mycorrhizal fungi attributes to recruited functional bacterial assembly - Yunjian Xu; Zhe Chen; Xiaoyu Li; Jing Tan; Fang Liu; Jianping Wu (Molecular Ecology, 2023)
Symbiosis with arbuscular mycorrhizal (AM) fungi improves plant nutrient capture from the soil, yet there is limited knowledge about the diversity, structure, functioning, and assembly processes of AM fungi‐related microbial communities. Here, 16S rRNA gene sequencing and metagenomic sequencing were used to detect bacteria in the rhizosphere of Lotus japonicus inoculated with and without AM fungi, and the L. japonicus mutant ljcbx (defective in symbiosis) inoculated with AM fungi in southern grassland soil. Our results show that AM symbiosis significantly increased bacterial diversity and promoted deterministic processes of bacterial community construction, suggesting that mycorrhizal symbiosis resulted in the directional enrichment of bacterial communities. AM fungi promoted the enrichment of nine bacteria, including Ohtaekwangia , Niastella , Gemmatimonas , Devosia , Sphingomonas , Novosphingobium , Opitutus , Lysobacter , Brevundimonas , which are positively correlated with NPK‐related parameters. Through a functional identification experiment, we found that six of these genera, including Brevundimonas , Lysobacter , Ohtaekwangia , Sphingomonas , Devosia , and Gemmatimonas , demonstrated the ability to mineralize organophosphate and dissolve inorganic phosphorus, nitrogen, and potassium. Our study revealed that AM fungi can regulate rhizosphere bacterial community assembly and attract specific rhizosphere bacteria to promote soil nutrient turnover in southern grasslands.

Precisely modulating the branching functional groups of MIL-53(Al) for highly efficient sequestration of uranium - Shuya Liu; Xinjie Ma; Yuxin Liu; Weiwei Chen; Yuejie Ai; Kexin Li; Xiushen Ye; Ming Fang; Xiaoli Tan (Journal of Environmental Chemical Engineering, 2023)

New Middle Jurassic record of fern genus Eboracia (Dicksoniaceae, Filicales) and its spatio-temporal distribution in China - Fang-Yu Li; Ning Tian; Zhen-Yu Wu; Zi-Kun Jiang; Xiao Tan (Palaeoworld, 2023)

A combination of umbilical cord mesenchymal stem cells and monosialotetrahexosy 1 ganglioside alleviates neuroinflammation in traumatic brain injury - Yanwei Fang; Wenna Qiu; Xin Li; Qianxu Jin; Hongshan Yan; Ning Yu; Jianhui Zhao; Yi Tan; Zongmao Zhao (Experimental Brain Research, 2023)

Association of exposure to perfluoroalkyl substances and risk of the acute coronary syndrome: A case-control study in Shijiazhuang Hebei Province - Haoran Li; Jinbo Chen; Jingchao Lu; Jing Yang; Zhenzhen Tan; Longfei Li; Fang Xiao; Ziwen An; Chaoying Ma; Yi Liu; Lei Wang; Xiaoguang Zhang; et al. (Chemosphere, 2023)

Multi-period optimization for CO2 sequestration potential of enhanced weathering using non-hazardous industrial wastes - Yanmei Zhang; Zhiwei Li; Kathleen B. Aviso; Raymond R. Tan; Fang Wang; Xiaoping Jia (Resources, Conservation and Recycling, 2023)

A magnetic adsorbent with metal-organic framework based on ammonium phosphomolybdenum heteropoly tungstate (AWP): Selective adsorption of Rb+ and Cs+ from aqueous resources and stripping with ammonium salts - Yanping Wang; Kexin Li; Liang Ma; Dezhen Fang; Miao Lu; Xiushen Ye; Haining Liu; Huifang Zhang; Xiaoli Tan; Zhijian Wu (Hydrometallurgy, 2023)

Synergetic effect of Ce/Zr for ethanol synthesis from syngas over Rh-based catalyst - Caixia Zhu; Kaizhuang Xu; Yuan Fang; Qian Lv; Kun Jiang; Huibo Zhao; Yang Chen; Peng Wang; Hua Yang; Lizhi Wu; Yu Tang; Li Tan (Fuel, 2023)

Improving the hydrogen evolution reaction activity of molybdenum-based heterojunction nanocluster capsules via electronic modulation by erbium–nitrogen–phosphorus ternary doping - Fang Tan; Yingtang Zhou; Hua Zhang; Pengliang Sun; Hongyi Li; Xijun Liu; Thomas Wågberg; Guangzhi Hu (Chemical Engineering Journal, 2023)

Nitrogen Removal Characteristics of a Marine Denitrifying Pseudomonas stutzeri BBW831 and a Simplified Strategy for Improving the Denitrification Performance Under Stressful Conditions - Jianhao Fang; Luqi Yan; Minghui Tan; Ganghui Li; Yingyin Liang; Kuntai Li (Marine Biotechnology, 2023)

In situ phytostabilization of arable soils severely contaminated with cadmium at Yangshuo, Southern China, using cash crops and amendments: a comprehensive performance evaluation - Bo-Fang Yan; Mei-Lin Yan; Xue Xiao; Rong-Liang Qiu; Yuan-Qing Chao; Yin-Xin Li; Su-Lian Lv; Zhong-Xin Tan; Ye-Tao Tang (Journal of Soils and Sediments, 2023)

Bio-solubilization of Yunnan lignite by Penicillium ortum MJ51 and characterization of its products - Shiying Li; Fang Li; Peipei Li; Yi Wang; Qiuzhe Shi; Xiaoqi Liu; Jinfang Tan; Yanlai Han (Fuel, 2023)

In vitro simulated digestion of and microbial characteristics in colonic fermentation of polysaccharides from four varieties of Tibetan tea - Yaowen Tan; Meiwen Li; Keyang Kong; Yushan Xie; Zhen Zeng; Zhengfeng Fang; Cheng Li; Bin Hu; Xinjie Hu; Caixia Wang; Saiyan Chen; Wenjuan Wu; et al. (Food Research International, 2023)

Lipid rafts may affect the coalescence of milk fat globules through phase transition after thermal treatment - Teng Wei; Yingchao Huang; Chen Weng; Fang Chen; Chaoli Tan; Wenqun Liu; Zeyuan Deng; Jing Li (Food Chemistry, 2023)

Solar ring mission: Building a panorama of the Sun and inner-heliosphere - Yuming Wang; Xianyong Bai; Changyong Chen; Linjie Chen; Xin Cheng; Lei Deng; Linhua Deng; Yuanyong Deng; Li Feng; Tingyu Gou; Jingnan Guo; Yang Guo; et al. (Advances in Space Research, 2023)

Identification of a stable major-effect quantitative trait locus for pre-harvest sprouting in common wheat (Triticum aestivum L.) via high-density SNP-based genotyping - Zhi Li; Yongyan Chen; Xia Ou; Mengning Wang; Nanxin Wang; Wei Li; Yawen Deng; Yixin Diao; Zixin Sun; Qinyi Luo; Xinli Li; Liqi Zhao; et al. (Theoretical and Applied Genetics, 2022)

mTORC1/C2 regulate spermatogenesis in Eriocheir sinensis via alterations in the actin filament network and cell junctions - Zhen-Fang Li; Shuang-Li Hao; Lan-Min Wang; Hong-Yu Qi; Jia-Ming Wang; Fu-Qing Tan; Wan-Xi Yang (Cell and Tissue Research, 2022)

Repeated Sevoflurane Exposures in Neonatal Rats Increased the Brain Vulnerability to Future Stress Exposure and Resulted in Fear Extinction Deficit - Ben-zhen Chen; Li-hua Jiang; Ling Tan; Wen-qin Zhou; Yu-chao Shang; Fang Li; Bin Liu (Neurotoxicity Research, 2022)

Ethnicity evaluation of ferric pyrophosphate citrate among Asian and Non-Asian populations: a population pharmacokinetics analysis - Lingxiao Zhang; Liangying Gan; Kexin Li; Panpan Xie; Yan Tan; Gang Wei; Xiaojuan Yuan; Raymond Pratt; Yongchun Zhou; Ai-Min Hui; Yi Fang; Li Zuo; et al. (European Journal of Clinical Pharmacology, 2022)
Purpose To evaluate the potential ethnic differences of ferric pyrophosphate citrate (FPC, Triferic) in healthy subjects and patients with hemodialysis-dependent stage 5 chronic kidney disease (CKD-5HD) and identify covariates that may influence pharmacokinetics (PK) of FPC. Methods Data were collected from 2 Asian and 4 non-Asian clinical studies involving healthy subjects and CKD-5HD patients. Three population PK models were developed: M1 for intravenous (IV) administration of FPC in healthy subjects; M2 for dialysate administration of FPC in CKD-5HD patients; M3 for pre-dialyzer administration of FPC in CKD-5HD patients. All the models were fitted to concentration versus time data of FPC using the nonlinear mixed effect approach with the NONMEM ® program. All statistical analyses were performed using SAS version 9.4. Results In total, 26 Asians and 65 non-Asians were included in the final model analysis database. Forty healthy subjects were administered FPC via intravenous (IV) route and 51 patients with CKD-5HD via dialysate ( N = 50) and pre-dialyzer blood circuit administration ( N = 51). The PK parameters of FPC IV were similar. The population PK model showed good parameter precision and reliability as shown by model evaluation, and no relevant influence of ethnicity on PK parameters was observed. In healthy subjects, the maximum observed plasma concentration (C max ) and area under the plasma concentration–time curve (AUC) decreased with increase in lean body mass (LBM) and the average serum total iron at 6 h before the baseline period (Fe av ), whereas, in both patient populations, C max and AUC decreased with increase in LBM and decrease in Fe baseline . Other factors such as gender, age, Fe av , and ethnicity had no influence on PK exposures in patients. The influence of LBM on PK exposures in patients was smaller than that in healthy subjects (ratio of AUC 0-24 for the 5th [68 kg] and 95th [45 kg] patient’s LBM was almost 1). The influence of Fe av and LBM on PK exposures was < 50%. Conclusion The population pharmacokinetics model successfully described the PK parameters of FPC in healthy subjects and CKD-5HD patients and were comparable between Asian and non-Asian populations.

Fertility conversion between cytoplasmic maintainer lines and restorer lines through molecular marker-assisted selection in pepper (Capsicum annuum L.) - Fu-Sen Ren; Hai-Feng Yang; Yu-Shun Jiao; Rui-Ping Zhang; Zhi-Wei Guo; He-Juan Liu; Qiang Sun; Xi-Jun Li; Xiu-Fang Tan; Bei Zhang; Jun-Qi Zhen; Yan-Qi Dong (Biologia, 2022)

First report of Nigrospora aurantiaca causing leaf spot on Pandanus amaryllifolius in Malaysia - Ying Wei Khoo; Hui Teng Tan; Yam Sim Khaw; Shi-Fang Li; Khim Phin Chong (Journal of Plant Pathology, 2022)

Effects of various spectral compositions on micro-polluted water purification and biofuel feedstock production using duckweed - Qi Li; Zhuolin Yi; Guili Yang; Yaliang Xu; Yanling Jin; Li Tan; Anping Du; Kaize He; Hai Zhao; Yang Fang (Environmental Science and Pollution Research, 2022)

Phenolic glycosides from Sanguisorba officinalis and their anti-inflammatory effects - Jin-feng Chen; Lu Tan; Feng Ju; Qi-xuan Kuang; Tian-long Yang; Fang Deng; Yu-cheng Gu; Li-shi Jiang; Yun Deng; Da-le Guo (Natural Product Research, 2022)

Preparation and In Vitro and In Vivo Evaluation of a Testosterone Film Forming Gel for the Treatment of Hypoactive Sexual Desire Disorder in Women - Jia Zeng; Tan-Fang Xie; Ting Huang; Fang Li; Zhi-Ping Wang; Ling-Lin Feng (AAPS PharmSciTech, 2022)

Fixed-bed column dynamics of ultrasound and Na-functionalized diatomite to remove phosphate from water - Junxiu Ye; Min Yang; Xuemei Ding; Wei Tan; Guizhen Li; Shuju Fang; Hongbin Wang (Environmental Science and Pollution Research, 2022)

Economic Evaluation of Water-Saving Irrigation Practices for Sustainable Sugarcane Production in Guangxi Province, China - Shan-Shan He; Yuan Zeng; Zhao-Xu Liang; Yan Jing; ShiYun Tang; Baoqing Zhang; Haifeng Yan; Song Li; Tinglin Xie; Fang Tan; Ming Li (Sugar Tech, 2021)

External evaluation of published population pharmacokinetic models of polymyxin B - Ya-qian Li; Kai-feng Chen; Jun-jie Ding; Hong-yi Tan; Nan Yang; Ya-qi Lin; Cui-fang Wu; Yue-liang Xie; Guo-ping Yang; Jing-Jing Liu; Qi Pei (European Journal of Clinical Pharmacology, 2021)

Early neutrophil-to-lymphocyte ratio is a prognostic marker in acute minor stroke or transient ischemic attack - Yi Luo; Lie-xin Xia; Zhi-lian Li; Ding-fang Pi; Xian-pei Tan; Qiang Tu (Acta Neurologica Belgica, 2021)

Two new nor-sesquiterpenoids from Fusarium tricinctum , an endophytic fungus isolated from Ligusticum chuanxiong - Yu-Mei Cao; Da-Le Guo; Meng-Ying Jin; Lu Tan; Tian-Long Yang; Fang Deng; Yu-Cheng Gu; Xiao-Hua Li; Zhi-Xing Cao; Yun Deng (Natural Product Research, 2021)

Influencing factors and physiochemical changes of embryogenesis through in vitro isolated microspore culture in Brassica species - Yan-Qi Dong; Yu-Hong Gao; Te Zhao; Guang-Qian Ren; Yan-Li Liu; Bin Guan; Rong-Xian Jin; Fei Gao; Yan-Li Zhang; Xiu-Fang Tan; Hong-Cai Zhu; Yu-Hong Zhang; et al. (Biologia, 2021)

The adsorption properties of functionalization vetiver grass-based activated carbon: the simultaneous adsorption of phosphate and nitrate - Jianmin Li; Xiuying Fang; Min Yang; Wei Tan; Haocheng Zhang; Yanyan Zhang; Guizhen Li; Hongbin Wang (Environmental Science and Pollution Research, 2021)

Prevalence of Depression or Depressive Symptoms in Patients with Narcolepsy: a Systematic Review and Meta-Analysis - Xiao Li; Larry D. Sanford; Qiang Zong; Ye Zhang; Lu Tan; Taomei Li; Rong Ren; Junying Zhou; Fang Han; Xiangdong Tang (Neuropsychology Review, 2021)

Antimonate removal by diatomite modified with Fe-Mn oxides: application and mechanism study - Qiu-Yi Dong; Yu-Chun Fang; Bin Tan; Aura Ontiveros-Valencia; Ang Li; He-Ping Zhao (Environmental Science and Pollution Research, 2021)

Epidemiology and HBGA-susceptibility investigation of a G9P[8] rotavirus outbreak in a school in Lechang, China - Lun-Ai Guo; Meng Zhang; Yu-zhen Hou; Haitao Hu; Ling Fang; Ming Tan; Qiong Huang; Hui Li; Li-Mei Sun; Xi Jiang; Wen-Fang Tan; Shixing Tang; et al. (Archives of Virology, 2020)

Synovial fibroblast-derived exosomal microRNA-106b suppresses chondrocyte proliferation and migration in rheumatoid arthritis via down-regulation of PDK4 - Dan Liu; Yuxuan Fang; Yujun Rao; Wei Tan; Wei Zhou; Xia Wu; Chunwang Zhang; Yu Zhang; Yanqing Liu; Masataka Sunagawa; Tadashi Hisamitsu; Guoqing Li (Journal of Molecular Medicine, 2020)

Review of Chinese atmospheric science research over the past 70 years: Synoptic meteorology - Zhiyong Meng; Fuqing Zhang; Dehai Luo; Zhemin Tan; Juan Fang; Jianhua Sun; Xueshun Shen; Yunji Zhang; Shuguang Wang; Wei Han; Kun Zhao; Lei Zhu; et al. (Science China Earth Sciences, 2019)

Magnetic nanoferromanganese oxides modified biochar derived from pine sawdust for adsorption of tetracycline hydrochloride - Jie Liang; Yilong Fang; Yuan Luo; Guangming Zeng; Jiaqin Deng; Xiaofei Tan; Ning Tang; Xuemei Li; Xinyue He; Chunting Feng; Shujing Ye (Environmental Science and Pollution Research, 2019)

Inhibition of YAP with siRNA prevents cartilage degradation and ameliorates osteoarthritis development - Yong Gong; Song-Jian Li; Rui Liu; Jian-Feng Zhan; Chao Tan; Yi-Fei Fang; Yan Chen; Bo Yu (Journal of Molecular Medicine, 2019)

Exogenous application of GA3 inactively regulates axillary bud outgrowth by influencing of branching-inhibitors and bud-regulating hormones in apple (Malus domestica Borkh.) - Ming Tan; Guofang Li; Xiaojie Liu; Fang Cheng; Juanjuan Ma; Caiping Zhao; Dong Zhang; Mingyu Han (Molecular Genetics and Genomics, 2018)

Characterizing the Mass Elevation Effect across the Tibetan Plateau - Fang Han; Bai-ping Zhang; Fang Zhao; Li Wan; Jing Tan; Tian Liang (Journal of Mountain Science, 2018)

Frond transformation system mediated by Agrobacterium tumefaciens for Lemna minor - Gui-Li Yang; Yang Fang; Ya-Liang Xu; Li Tan; Qi Li; Yang Liu; Fan Lai; Yan-Ling Jin; An-Ping Du; Kai-Ze He; Xin-Rong Ma; Hai Zhao (Plant Molecular Biology, 2018)

Molecular role of cytokinin in bud activation and outgrowth in apple branching based on transcriptomic analysis - Guofang Li; Ming Tan; Fang Cheng; Xiaojie Liu; Siyan Qi; Hongfei Chen; Dong Zhang; Caiping Zhao; Mingyu Han; Juanjuan Ma (Plant Molecular Biology, 2018)

Front Cover - James A. Lutz; Tucker J. Furniss; Daniel J. Johnson; Stuart J. Davies; David Allen; Alfonso Alonso; Kristina J. Anderson‐Teixeira; Ana Andrade; Jennifer Baltzer; Kendall M. L. Becker; Erika M. Blomdahl; Norman A. Bourg; et al. (Global Ecology and Biogeography, 2018)

Global importance of large‐diameter trees - James A. Lutz; Tucker J. Furniss; Daniel J. Johnson; Stuart J. Davies; David Allen; Alfonso Alonso; Kristina J. Anderson‐Teixeira; Ana Andrade; Jennifer Baltzer; Kendall M. L. Becker; Erika M. Blomdahl; Norman A. Bourg; et al. (Global Ecology and Biogeography, 2018)
Aim To examine the contribution of large‐diameter trees to biomass, stand structure, and species richness across forest biomes. Location Global. Time period Early 21st century. Major taxa studied Woody plants. Methods We examined the contribution of large trees to forest density, richness and biomass using a global network of 48 large (from 2 to 60 ha) forest plots representing 5,601,473 stems across 9,298 species and 210 plant families. This contribution was assessed using three metrics: the largest 1% of trees ≥ 1 cm diameter at breast height (DBH), all trees ≥ 60 cm DBH, and those rank‐ordered largest trees that cumulatively comprise 50% of forest biomass. Results Averaged across these 48 forest plots, the largest 1% of trees ≥ 1 cm DBH comprised 50% of aboveground live biomass, with hectare‐scale standard deviation of 26%. Trees ≥ 60 cm DBH comprised 41% of aboveground live tree biomass. The size of the largest trees correlated with total forest biomass ( r 2 = .62, p r 2 = .45, p r 2 = .33, p r 2 = .17, p = .002). The concentration of biomass in the largest 1% of trees declined with increasing absolute latitude ( r 2 = .46, p r 2 = .31, p r 2 = .26, p Main conclusions Because large‐diameter trees constitute roughly half of the mature forest biomass worldwide, their dynamics and sensitivities to environmental change represent potentially large controls on global forest carbon cycling. We recommend managing forests for conservation of existing large‐diameter trees or those that can soon reach large diameters as a simple way to conserve and potentially enhance ecosystem services.

CyberConnector: a service-oriented system for automatically tailoring multisource Earth observation data to feed Earth science models - Ziheng Sun; Liping Di; Haosheng Hao; Xiaoqing Wu; Daniel Q. Tong; Chen Zhang; Cora Virgei; Hui Fang; Eugene Yu; Xicheng Tan; Peng Yue; Li Lin (Earth Science Informatics, 2018)

Efficient Using Durian Shell Hydrolysate as Low-Cost Substrate for Bacterial Cellulose Production by Gluconacetobacter xylinus - Mu-Tan Luo; Cheng Zhao; Chao Huang; Xue-Fang Chen; Qian-Lin Huang; Gao-Xiang Qi; Lan-Lan Tian; Lian Xiong; Hai-Long Li; Xin-De Chen (Indian Journal of Microbiology, 2017)

MXR7 facilitates liver cancer metastasis via epithelial-mesenchymal transition - Guishuai Lv; Yexiong Tan; Hongwei Lv; Tian Fang; Changzheng Wang; Ting Li; Yanting Yu; Congli Hu; Wen Wen; Hongyang Wang; Wen Yang (Science China Life Sciences, 2017)

A new putative deltapartitivirus recovered from Dianthus amurensis - Hongliu An; Guanlin Tan; Guihong Xiong; Meirong Li; Shouguo Fang; Saif Ul Islam; Songbai Zhang; Fan Li (Archives of Virology, 2017)

A novel Enterovirus 96 circulating in China causes hand, foot, and mouth disease - Yi Xu; Yisuo Sun; Jinmin Ma; Shuru Zhou; Wei Fang; Jiawei Ye; Limei Tan; Jingkai Ji; Dan Luo; Liqiang Li; Jiandong Li; Chunxiao Fang; et al. (Virus Genes, 2017)

Genome-wide association analysis of seed germination percentage and germination index in Brassica napus L. under salt and drought stresses - Min Tan; Fang Liao; Lintao Hou; Jia Wang; Lijuan Wei; Hongju Jian; Xinfu Xu; Jiana Li; Liezhao Liu (Euphytica, 2017)

Abnormal O-GlcNAcylation of Pax3 Occurring from Hyperglycemia-Induced Neural Tube Defects Is Ameliorated by Carnosine But Not Folic Acid in Chicken Embryos - Rui-Rong Tan; Yi-Fang Li; Shi-Jie Zhang; Wen-Shan Huang; Bun Tsoi; Dan Hu; Xin Wan; Xuesong Yang; Qi Wang; Hiroshi Kurihara; Rong-Rong He (Molecular Neurobiology, 2017)

Targeting Interleukin-1 beta to Suppress Sympathoexcitation in Hypothalamic Paraventricular Nucleus in Dahl Salt-Sensitive Hypertensive Rats - Jie Qi; Xiu-Fang Zhao; Xiao-Jing Yu; Qiu-Yue Yi; Xiao-Lian Shi; Hong Tan; Xiao-Yan Fan; Hong-Li Gao; Li-Ying Yue; Zhi-Peng Feng; Yu-Ming Kang (Cardiovascular Toxicology, 2016)

Isolation and identification of polyphenols from Marsilea quadrifolia with antioxidant properties in vitro and in vivo - Yuan Zhang; Hai-Yan Tian; Ya-Fang Tan; Yuk-Lau Wong; Hoi Yan Wu; Jun-Feng Jia; Guo-En Wang; Jing-Jing Gao; Yi-Fang Li; Hiroshi Kurihara; Pang-Chui Shaw; Ren-Wang Jiang (Natural Product Research, 2016)

Transcriptome sequencing discovers genes related to fatty acid biosynthesis in the seeds of Eucommia ulmoides - Yan-zhi Feng; Lu Wang; Jian-min Fu; Ta-na Wuyun; Hong-yan Du; Xiao-feng Tan; Feng Zou; Fang-dong Li (Genes & Genomics, 2016)

Association study of protamine 2 (PRM2) gene polymorphism with male infertility in Chinese Han population - Xuemei Yang; Fang Liu; Jun Li; Yaman Song; Yuzhe Tan (Genes & Genomics, 2016)

Identification and molecular characterization of Panax notoginseng virus A, which may represent an undescribed novel species of the genus Totivirus, family Totiviridae - Lingfang Guo; Xin Yang; Wei Wu; Guanlin Tan; Shouguo Fang; Songbai Zhang; Fan Li (Archives of Virology, 2016)

Phytosterol content and the campesterol:sitosterol ratio influence cotton fiber development: role of phytosterols in cell elongation - Shasha Deng; Ting Wei; Kunling Tan; Mingyu Hu; Fang Li; Yunlan Zhai; Shue Ye; Yuehua Xiao; Lei Hou; Yan Pei; Ming Luo (Science China Life Sciences, 2016)

First survey of parasitic helminths of goats along the Han River in Hubei Province, China - Xin Yang; Robin B. Gasser; Rui Fang; Jinrong Zeng; Kaixiang Zhu; Mingwei Qi; Zongze Zhang; Li Tan; Weiqiang Lei; Yanqin Zhou; Junlong Zhao; Min Hu (Acta Parasitologica, 2016)
Diseases caused by parasitic helminths cause considerable production and economic losses in livestock worldwide. Understanding the epidemiology of these parasites has important implications for controlling them. The main purpose of the present study was to estimate the prevalence of key parasitic helminths in goats along the Han River in Zhanggang, Hubei Province (from January to December 2014). We used faecal flotation and sedimentation techniques as well as PCR-based DNA sequencing to detect and identify helminths. Results showed that the prevalence of helminths was high throughout the year, particularly for gastrointestinal nematodes. These first findings provide useful baseline information for goat helminths in Zhanggang, and a starting point for the implementation of control programs. With an increased expansion of the goat industry in China, the findings also emphasise the need to undertake prevalence surveys in other regions of China where extensive farming practices are used.

Integrating input–output models with pinch technology for enterprise sustainability analysis - Xiaoping Jia; Zhiwei Li; Fang Wang; Dominic C. Y. Foo; Raymond R. Tan (Clean Technologies and Environmental Policy, 2015)

Genetic map and QTL controlling fiber quality traits in upland cotton (Gossypium hirsutum L.) - Zhaoyun Tan; Xiaomei Fang; Shiyi Tang; Jian Zhang; Dajun Liu; Zhonghua Teng; Ling Li; Huijuan Ni; Fengmin Zheng; Dexin Liu; Tingfu Zhang; Andrew H. Paterson; et al. (Euphytica, 2015)

CTFS ‐Forest GEO : a worldwide network monitoring forests in an era of global change - Kristina J. Anderson‐Teixeira; Stuart J. Davies; Amy C. Bennett; Erika B. Gonzalez‐Akre; Helene C. Muller‐Landau; S. Joseph Wright; Kamariah Abu Salim; Angélica M. Almeyda Zambrano; Alfonso Alonso; Jennifer L. Baltzer; Yves Basset; Norman A. Bourg; et al. (Global Change Biology, 2015)
Global change is impacting forests worldwide, threatening biodiversity and ecosystem services including climate regulation. Understanding how forests respond is critical to forest conservation and climate protection. This review describes an international network of 59 long‐term forest dynamics research sites ( CTFS ‐Forest GEO ) useful for characterizing forest responses to global change. Within very large plots (median size 25 ha), all stems ≥1 cm diameter are identified to species, mapped, and regularly recensused according to standardized protocols. CTFS ‐Forest GEO spans 25°S–61°N latitude, is generally representative of the range of bioclimatic, edaphic, and topographic conditions experienced by forests worldwide, and is the only forest monitoring network that applies a standardized protocol to each of the world's major forest biomes. Supplementary standardized measurements at subsets of the sites provide additional information on plants, animals, and ecosystem and environmental variables. CTFS ‐Forest GEO sites are experiencing multifaceted anthropogenic global change pressures including warming (average 0.61 °C), changes in precipitation (up to ±30% change), atmospheric deposition of nitrogen and sulfur compounds (up to 3.8 g N m −2 yr −1 and 3.1 g S m −2 yr −1 ), and forest fragmentation in the surrounding landscape (up to 88% reduced tree cover within 5 km). The broad suite of measurements made at CTFS ‐Forest GEO sites makes it possible to investigate the complex ways in which global change is impacting forest dynamics. Ongoing research across the CTFS ‐Forest GEO network is yielding insights into how and why the forests are changing, and continued monitoring will provide vital contributions to understanding worldwide forest diversity and dynamics in an era of global change.

Two new bufadienolides from the rhizomes of Helleborus thibetanus with inhibitory activities against prostate cancer cells - Wei Cheng; Ya-Fang Tan; Hai-Yan Tian; Xiang-Wen Gong; Ke-Li Chen; Ren-Wang Jiang (Natural Product Research, 2014)

Differential responses to short-term salinity stress of heat-tolerant cherry tomato cultivars grown at high temperatures - Fang-Yi Liu; Kuo-Tan Li; Wen-Ju Yang (Horticulture, Environment, and Biotechnology, 2014)

Using proteomic analysis to find the proteins involved in resistance against Sclerotinia sclerotiorum in adult Brassica napus - Li Wen; Tai-Long Tan; Jia-Bin Shu; Ying Chen; Ying Liu; Zhong-Fang Yang; Qiu-Ping Zhang; Ming-Zhi Yin; Jun Tao; Chun-Yun Guan (European Journal of Plant Pathology, 2013)

Screening of high α-arbutin producing strains and production of α-arbutin by fermentation - Chun-Qiao Liu; Li Deng; Peng Zhang; Shu-Rong Zhang; Luo Liu; Tao Xu; Fang Wang; Tian-Wei Tan (World Journal of Microbiology and Biotechnology, 2013)

Proteomic and physiological analyses reveal detoxification and antioxidation induced by Cd stress in Kandelia candel roots - Zhao-Xia Weng; Ling-Xia Wang; Fang-lin Tan; Li Huang; Jian-Hong Xing; Shi-Pin Chen; Chi-Lien Cheng; Wei Chen (Trees, 2013)

The Antitumor Effect of a New Docetaxel-Loaded Microbubble Combined with Low-Frequency Ultrasound In Vitro: Preparation and Parameter Analysis - Shu-Ting Ren; Yi-Ran Liao; Xiao-Ning Kang; Yi-Ping Li; Hui Zhang; Hong Ai; Qiang Sun; Jing Jing; Xing-Hua Zhao; Li-Fang Tan; Xin-Liang Shen; Bing Wang (Pharmaceutical Research, 2013)

Lack of effect of continuous glycyrrhizin administration on the pharmacokinetics of the P-glycoprotein substrate talinolol in healthy volunteers - Miao Yan; Ping-Fei Fang; Huan-De Li; Ping Xu; Yi-Ping Liu; Feng Wang; Hua-Lin Cai; Qin-You Tan (European Journal of Clinical Pharmacology, 2013)

Cloud point extraction of aloe anthraquinones based on non-ionic surfactant aqueous two-phase system - Zhi-Jian Tan; Fen-Fang Li; Jian-Min Xing (Natural Product Research, 2012)

Genetic variant in TP63 on locus 3q28 is associated with risk of lung adenocarcinoma among never-smoking females in Asia - H. Dean Hosgood; Wen-Chang Wang; Yun-Chul Hong; Jiu-Cun Wang; Kexin Chen; I-Shou Chang; Chien-Jen Chen; Daru Lu; Zhihua Yin; Chen Wu; Wei Zheng; Biyun Qian; et al. (Human Genetics, 2012)

Isolation and Identification of Endophytic Fungi in Roots of Nine Holcoglossum Plants (Orchidaceae) Collected from Yunnan, Guangxi, and Hainan Provinces of China - Xiao-Ming Tan; Xiao-Mei Chen; Chun-Lan Wang; Xiao-Hua Jin; Jin-Long Cui; Juan Chen; Shun-Xing Guo; Li-Fang Zhao (Current Microbiology, 2012)

Development of a simple and efficient transformation system for the basidiomycetous medicinal fungus Ganoderma lucidum - Liang Shi; Xing Fang; Mengjiao Li; Dashuai Mu; Ang Ren; Qi Tan; Mingwen Zhao (World Journal of Microbiology and Biotechnology, 2012)

Characteristics and evolution of the PUF gene family in Bombyx mori and 27 other species - Chun-Dong Zhang; Min-Hui Pan; Juan Tan; Fang-Fang Li; Jun Zhang; Ting-Ting Wang; Cheng Lu (Molecular Biology Reports, 2012)

Aglaianine, a new bisamide from Aglaia abbreviata - Ling Zhang; Li-Hua Wang; Yan-Fang Yang; Shu-Ming Yang; Jian-Hui Zhang; Chang-Heng Tan (Natural Product Research, 2011)

The impact of positive cancer family history on the clinical features and outcome of patients with non-small cell lung cancer - Ning Li; Kang Shao; Zhaoli Chen; Bin Qiu; Zhen Wang; Fengwei Tan; Jiwen Wang; Xiaogang Tan; Baozhong Li; Meihua Xiong; Fang Zhou; Jie He (Familial Cancer, 2011)

High-mobility group box 1 exacerbates concanavalin A-induced hepatic injury in mice - Quan Gong; Hui Zhang; Jun-hua Li; Li-hua Duan; Shan Zhong; Xiao-ling Kong; Fang Zheng; Zheng Tan; Ping Xiong; Gang Chen; Min Fang; Fei-li Gong (Journal of Molecular Medicine, 2010)

The effects of CYP2C9 and CYP2C19 genetic polymorphisms on the pharmacokinetics and pharmacodynamics of glipizide in Chinese subjects - Bo Tan; Yi-Fan Zhang; Xiao-Yan Chen; Xiao-Hua Zhao; Guo-Xin Li; Da-Fang Zhong (European Journal of Clinical Pharmacology, 2010)

Inhibitory effect of reinioside C on monocyte–endothelial cell adhesion induced by oxidized low-density lipoprotein via inhibiting NADPH oxidase/ROS/NF-κB pathway - Yong-Ping Bai; Chang-ping Hu; Mei-Fang Chen; Kang-Ping Xu; Gui-Shan Tan; Rui-Zhen Shi; Yuan-Jian Li; Guo-Gang Zhang (Naunyn-Schmiedeberg's Archives of Pharmacology, 2009)

Genome-wide association scan for stature in Chinese: evidence for ethnic specific loci - Shu-Feng Lei; Tie-Lin Yang; Li-Jun Tan; Xiang-Ding Chen; Yan Guo; Yan-Fang Guo; Liang Zhang; Xiao-Gang Liu; Han Yan; Feng Pan; Zhi-Xin Zhang; Yu-Mei Peng; et al. (Human Genetics, 2009)

Culturable and molecular phylogenetic diversity of microorganisms in an open-dumped, extremely acidic Pb/Zn mine tailings - Gui-Liang Tan; Wen-Sheng Shu; Kevin B. Hallberg; Fang Li; Chong-Yu Lan; Wen-Hua Zhou; Li-Nan Huang (Extremophiles, 2008)

Evolutionary and functional study of the CDPK gene family in wheat (Triticum aestivum L.) - Ai-Li Li; Yuan-Fang Zhu; Xiao-Mei Tan; Xiang Wang; Bo Wei; Han-Zi Guo; Zeng-Lin Zhang; Xiao-Bo Chen; Guang-Yao Zhao; Xiu-Ying Kong; Ji-Zeng Jia; Long Mao (Plant Molecular Biology, 2008)

A novel thioredoxin reductase inhibitor inhibits cell growth and induces apoptosis in HL-60 and K562 cells - Zuo-fu Peng; Lin-xiang Lan; Fang Zhao; Jing Li; Qiang Tan; Han-wei Yin; Hui-hui Zeng (Journal of Zhejiang University-SCIENCE B, 2008)